68Ga–Prostate-Specific Membrane Antigen PET–Positive Paget Bone Disease With Metastatic Prostatic Carcinoma. (September 2020) - Engur, Ceren Ozge; Turoglu, Halil Turgut; Ozguven, Salih; Tanidir, Yiloren; Erdil, Tanju Yusuf
Abstract : Abstract: Paget bone disease is a chronic benign bone disease characterized by excessive and abnormal bone remodeling. The scintigraphic and bone SPECT/CT hybrid imaging appearances of the affected bone(s) depend on the stage of the disease. We report the case of a patient newly diagnosed with prostate cancer who was found to have multiple osseous metastases, with coexisting Paget disease in the left hemipelvis diagnosed because of typical scintigraphic and SPECT/CT appearance. 68 Ga–prostate-specific membrane antigen PET/CT was also performed for initial staging. Pagetoid bones showed increased prostate-specific membrane antigen uptake like skeletal metastases.